Group Method of Data Handling with Artificial Bee Colony in Combining Forecasts - Yahya, Nurhaziyatul Adawiyah; Samsudin, Ruhaidah; Darmawan, Irfan; Shabri, Ani; Kasim, Shahreen (International Journal of Integrated Engineering, 2018)
In this study, the use of Artificial Intelligence (AI) algorithm to combine several time series forecasts is presented. This study is done by combining individual forecasts of Group Method of Data Handling models using the weighted-based combine approach. The weights for each individual model are calculated using Artificial Bee Colony algorithm. In order to evaluate the proposed model, this study tested the proposed model on the International Airline Passengers data, and the performances are calculated using mean square error (MSE), mean average error (MAE) and mean average percentage error (MAPE). The accuracy of the proposed model is compared to the individual models and the models implemented in previous literatures. The results revealed that the proposed model is able to produce significantly accurate forecasts